Eksplorasi Perilaku Vandalisme dan Ekologi Sosial Remaja Pada Komunitas Me and Art Kota Medan - Fitria Akbar Kani Chaniago; Asiah Asiah (CV. Eracita Grup, 2026)
Vandalism among urban adolescents is frequently reduced to mere juvenile delinquency, often ignoring the underlying sociological and psychological roots. This study aims to critically analyze the forms of vandalism and unravel the role of social ecology (family, peers, and society) that triggers the Me and Art adolescent community to vandalize public facilities in Medan City. Utilizing a qualitative approach with an embedded single-case design, this research involved three adolescents (NK, RS, and IY) as the main subjects, selected through purposive sampling, and was supported by source triangulation from local residents and community leaders. Data collection was conducted through in-depth unstructured interviews, passive participatory observation, and documentation studies with ethical mitigation applied. The findings indicate that the vandalism committed by this community is not a random act; rather, it is structured into tactical vandalism (for group existence) and vindictive vandalism (as retaliation against social rejection). The social environment plays a dual role: dysfunctional families create a vacuum of affection, which is subsequently filled by the peer group (the Me and Art community) that normalizes deviant behavior through the transmission of subcultural values. This study concludes that vandalism within this community serves as a silent protest and a distorted pursuit of identity. Based on these findings, community counseling approaches and directed expressive arts therapy interventions are recommended to channel adolescents' aggressive energy into constructive endeavors.